(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article examines the role of national values in ensuring sustainable development of society. National values are a system of spiritual, cultural, moral and social guidelines that shape the identity of the people and determine the strategy of its development. In the context of globalization and modernization, the preservation and adaptation of national values are becoming important factors of stability and progress. The article analyzes theoretical approaches to the concept of national values, their influence on social, economic and political processes, and provides an overview of scientific research in this area.